HUBUNGAN SELF EFFICACY DENGAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS V SD SE-GUGUS 6 KECAMATAN TAMPAN KOTA PEKANBARU - Ali Purningsih; Syahrilfuddin '; Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research was to know wheter there realtion between self efficacy and motivation of learning mathematics 5th grade of elementary school in 6th regional of Kecamatan Tampan, Pekanbaru CIty. Sample research determined by sampling random, election of sample relied on technique of Cluster Sampling, so that in this research is specified by 86 respondents. Data collecting conducted by using questioner. This research used correlation of Pearson's product moment. The analysis of the research data obtained by the coefficient correlation between self efficacy with motivation of learning mathematics of 0,77 with the p value of 0,000. It has shown that there was a significant relation between self efficacy with motivation of learning mathematics elementary students, the increase of self efficacy, followed by an increase in motivation of learning mathematics 5th grade of elementary school in 6th regional of Kecamatan Tampan, Pekanbaru City.Key Words: self efficacy, motivation of learning mathematics